2019
DOI: 10.1007/s10903-019-00960-z
|View full text |Cite
|
Sign up to set email alerts
|

Nepali Migrant Workers and the Need for Pre-departure Training on Mental Health: A Qualitative Study

Abstract: Every year around 1000 Nepali migrant workers die abroad. Every one in three females and one in ten males commit suicide, reflecting a high mental health risk among Nepali migrant workers. This study aims to identify triggers of mental ill-health among Nepali migrant workers and their perceptions on the need of mental health components in the pre-departure orientation programme. We conducted five focus group discussions (FGD) and seven in-depth interviews with Nepali migrant workers and eight semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Consistent with the findings from previous studies [24,25], this study also found that mental health problems among migrant workers persist as a result of poor living and work environments. On many occasions, migrants’ experienced their psychosocial health threatened due to communication barriers, abuse and exploitation by supervisors.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings from previous studies [24,25], this study also found that mental health problems among migrant workers persist as a result of poor living and work environments. On many occasions, migrants’ experienced their psychosocial health threatened due to communication barriers, abuse and exploitation by supervisors.…”
Section: Discussionsupporting
confidence: 92%
“… 21 One study analysed Nepalese government’s report and looked at 1354 deaths in Nepalese migrant workers, of which 8.5% were due to suicide. 35 The fifth quality qualitative study reported various mental health problems among the workers including loneliness, social isolation, tensions, anxiety, attempt to suicide 38 ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 7 The fourth study reported that only insurance 68% of the workers had health insurance abroad and only 20% underwent regular health check-up. 37 In the qualitative study, participants reported poor access to mental health services related, mainly related to communication problems, and stigma to mental health 38 ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the suicide risk among migrants is complex, as suicidal ideation and/or suicide attempts are influenced by a myriad of socio-cultural and economic factors in both the country of origin and destination, including demographic factors such as age and gender and mental health problems including depression, anxiety, and hopelessness [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Migrant workers as a vulnerable group also experience social exclusion and mental health issues in host countries, which further lead to higher risk for suicide ideation and attempt [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%